Sexual behaviour and contraceptie usage of secondary school adolescents in Ibadan, Nigeria (2007)
Objective To determine the prevalence and pattern of sexual activity as well as the contraceptive practices among the selected secondary school adolescents in Ibadan, Nigeria. Methods A descriptive cross-sectional study was conducted among the selected senior secondary school students in Ibadan, Nigeria, following a stratified multistage random sampling technique. Results There were 695 respondents out of which the females constituted 51% and the males were 49%. Less than one third (28.3%) of the respondents have had previous sexual exposure at the time of the study. The median age of sexual debut among the sexually exposed was 15 years in both the males and the females. Bivariate analysis of sociodemographic characteristics of respondents with previous sexual exposure showed that, sex, religion, father’s and mother’s educational background and level of class were statistically significant(P<0.001). Further analysis using logistic regression model revealed that male respondents were 3 times more likely than females (95% CI 1.92-4.56) to have had sexual experience while those whose mother had tertiary educational background were less likely to have had previous sexual experience compared to those with secondary and lower educational background (OR= 1.76, 95% CI 1.11- 2.77). Of all the sociodemographic characteristics of respondents considered with the age of sexual partners using bivariate analysis showed that only level of class was significant (P=0.018). Less than half of the sexually active males (44.2%) were using modern method (male condom) of contraception, while 54.4% of the sexually active females were using different types of modern methods. Conclusion It is quite obvious that risky sexual behaviors are in practice among the secondary school students studied and by extension in the country. It therefore means that reproductive health issues especially concerning the adolescents will have to be openly discussed by all with our youths while abstinence/chastity should be cherished